Fostering healthcare innovation: a qualitative study of dental implant product development by Thai university researchers - Sutti Sooampon; Pagaporn Pantuwadee Pisarnturakit; Sireerat Sooampon (International Journal of Health Governance, 2021)
Purpose This study investigated the conditions required to foster healthcare innovation. Due to the limited research and development (R&D) capability of the Thai private sector, universities are increasingly expected to be emerging sources of healthcare products. However, the lack of experience in research commercialization requires that whether and how Thai university researchers can serve this mission be explored. Design/methodology/approach A promising dental implant product development project was investigated using the single-case research methodology. In-depth interviews were conducted with three key members involved in this innovative project. Questions concerning how a team of university researchers could embark on and overcome the obstacles encountered during their entrepreneurial project were asked. Based on the conceptual foundation of academic entrepreneurship, primary and additional secondary data were analyzed to acquire knowledge of academic entrepreneurship in healthcare in an emerging economy. Findings Healthcare inequality has generated entrepreneurial initiatives by healthcare researchers to develop low-cost dental implants. However, their efforts have been insufficient to progress to the commercialization stage. An informal relationship among socially oriented partners, including interdisciplinary experts, not-for-profit-oriented manufacturers and early adopters contributed to this project's success. Originality/value To foster healthcare innovation, the authors’ micro-level evidence of a socially oriented partnership on an informal basis indicates the need for inter-professional governance that maintains a cross-organizational environment between healthcare researchers and external parties. The future contributions to innovation management by healthcare professionals should be enhanced. A socially entrepreneurial model of healthcare innovation is suggested for further consideration as an enabling policy option for inter-professional partnership in emerging economies.
Keywords: Dental Education, Practice, Research; Entrepreneurship Studies and Influences; Biomedical and Engineering Education